2020
DOI: 10.1007/s00464-020-07532-5
|View full text |Cite
|
Sign up to set email alerts
|

Poorly differentiated is more significant than signet ring cell component for lymph node metastasis in mixed-type early gastric cancer: a retrospective study from a large-volume hospital

Abstract: Objective The purpose of this study was to explore the role of different undifferentiated components in the lymph node metastasis (LNM) of early mixed gastric cancer. Methods A total of 1596 patients with EGC who underwent gastrectomy were divided into four types: pure differentiated (PD), pure poorly differentiated (Poorly D), pure signet ring cell carcinoma (SRC), and mixed. Mixed type was classified into four subtypes: differentiated-predominant type mixed with poorly differentiated component (MD-P), poorly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Poor differentiation already been incorporated into the AJCC classi cation for esophageal cancer as histologic Grade 3. Poor differentiation was also found to be a predictor for deeper tumor invasion and lymph nodes metastasis in gastric cancer [41,42].…”
Section: Discussionmentioning
confidence: 89%
“…Poor differentiation already been incorporated into the AJCC classi cation for esophageal cancer as histologic Grade 3. Poor differentiation was also found to be a predictor for deeper tumor invasion and lymph nodes metastasis in gastric cancer [41,42].…”
Section: Discussionmentioning
confidence: 89%
“…One publication was excluded due to a different definition of PU (only undifferentiated components vs more than 90% undifferentiated components) 15. After the thorough screening, 12 publications9 10 13 14 16–23 with 5644 patients were included for this meta-analysis, and the basic summarising information from these articles is shown in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Certain reports have claimed that MU EGC has a significantly higher risk of LNM than PU EGC 9. However, Chen et al reported that MU EGC did not show an increase in the incidence of LNM compared with PU EGC 10. Additionally, according to the treatment guidelines of the Japanese Gastric Cancer Association,11 MU and PU EGC are collectively treated as undifferentiated-type EGC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that patients with well-moderately differentiated GC and poorly differentiated GC have different sensitivity to chemotherapy regimens and show differences in clinical characteristics, such as poorly differentiated GC has a poor prognosis and a high degree of malignancy ( 33 , 61 ). The treatment effect for poorly differentiated GC remains poor ( 33 , 61 ) and it has been demonstrated that poorly differentiated GC is a hotspot in clinical treatment research ( 35 ). GC is divided into early GC (stage I and II) and advanced GC (stage III or higher tumors) ( 36 38 ), and there are differences in treatment and surgical methods between early and advanced GC ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Tumor Node Metastasis (TNM) staging of tumor was classified according to the American Joint Committee on Cancer Staging System (8 th edition) ( 31 ). According to WHO's fifth edition of gastric cancer differentiation standard ( 32 ), the clinical characteristics and prognosis of patients with GC with well-moderately differentiated and patients with GC with poorly-signet differentiated were different ( 33 35 ), patients with GC with regards to histological grade were divided into the well-moderately group and poorly-signet group. According to the American Joint Committee on Cancer Staging System (8 th edition) ( 31 ), and the differences in treatment and surgical methods between early gastric cancer group (stage I and II) and advanced gastric cancer group (stage III or higher tumors) ( 36 40 ), patients with GC with regards to pathological stage were divided into the early GC group (stage I and II) and advanced GC group (stage III or higher tumors).…”
Section: Methodsmentioning
confidence: 99%